2021
DOI: 10.1002/ange.202102224
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Mechanism of Action of the Cell Wall Targeting Antibiotic Hypeptin

Abstract: Hypeptin is a cyclodepsipeptide antibiotic produced by Lysobacter sp. K5869, isolated from an environmental sample by the iChip technology, dedicated to the cultivation of previously uncultured microorganisms. Hypeptin shares structural features with teixobactin and exhibits potent activity against a broad spectrum of gram-positive pathogens. Using comprehensive in vivo and in vitro analyses, we show that hypeptin blocks bacterial cell wall biosynthesis by binding to multiple undecaprenyl pyrophosphate-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…For example, β-hydroxytyrosine is an nsAA found in several cyclic peptide natural products, including the antibiotic hypeptin (Figure 1, 1). [7] We initially attempted to directly generate β-hydroxytyrosine via an ObiH-catalyzed aldol reaction with 4-hydroxybenzaldehyde, but observed no product formation. This lack of reactivity has been mirrored in other TA systems, but no strategy to access these products has been put forth.…”
Section: Chembiochemmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, β-hydroxytyrosine is an nsAA found in several cyclic peptide natural products, including the antibiotic hypeptin (Figure 1, 1). [7] We initially attempted to directly generate β-hydroxytyrosine via an ObiH-catalyzed aldol reaction with 4-hydroxybenzaldehyde, but observed no product formation. This lack of reactivity has been mirrored in other TA systems, but no strategy to access these products has been put forth.…”
Section: Chembiochemmentioning
confidence: 99%
“…[1] In particular, these molecules are prominent intermediates in the biosynthesis of cyclic peptide and small molecule antibiotics, such as the compounds hypeptin (1), katanosin B (2), and chloramphenicol (4), as well as other bioactive molecules (e.g., 3). [7][8][9] A variety of organocatalytic methods have been developed to install the β-hydroxyl group, often via the aldol addition of a glycyl Cα-nucleophile into various aldehydes. [10][11][12][13][14][15] These methods are effective at generating β-hydroxy-α-amino acids, but often require orthogonal, multi-step protecting group strategies to produce the desired product which can increase costs and reduce overall yields.…”
Section: Introductionmentioning
confidence: 99%
“…PB-6269 in 1989 and was recently produced in larger quantities by application of the same iChip technology that facilitated the discovery of teixobactin. 158 Containing three fewer amino acids that teixobactin, hypeptin is an octadepsipeptide containing a C-terminal macrocyclic tetrapeptide with four of its eight residues being b-hydroxylated. Given its similarities to teixobactin in both structure and activity, Schneider and co-workers speculated that hypeptin exerts its bactericidal activity through a similar mechanism.…”
Section: Teixobactinmentioning
confidence: 99%
“…The binding was considerably stronger (four-fold) to lipid I and lipid II than C 55 PP and lipid III WTA . 158 Clovibactin, also known as Novo29, is another teixobactin-like octadepsipeptide that was recently disclosed in the patent literature. 160 While clovibactin is reported to have potent anti-Gram-positive activity, as of yet no mechanistic studies have been reported.…”
Section: Teixobactinmentioning
confidence: 99%
“…Hypeptin, by co-targeting lipid II and wall teichoic acids (WTA) lipid intermediates, causes the weakening of the peptidoglycan structure and liberation of autolysins, synergistically leading to cell lysis and death. 103…”
Section: Lipodepsipeptides As Antibioticsmentioning
confidence: 99%